Effect of Micro- and Nanomagnetite on Printing Toner Properties. (19th January 2014) - Ataeefard, Maryam; Ghasemi, Ebrahim; Ebadi, Mona
Abstract : Toner is a main component of electrophotographic printing and copying processes. One of the most important ingredients of toner is magnetite (Fe3 O4 ) which provides the tribocharging property for toner particles. In this study, nano- and microparticles of Fe3 O4 were synthesized using the coprecipitation method and different amounts of lauric acid as a surfactant. The synthesized nano and micro Fe3 O4 was then used as the charge control agent to produce toner by emulsion aggregation. The Fe3 O4 and toner were characterized by X-ray powder diffraction (XRD), atomic gradient force magnetometry (AGFM), dynamic laser scattering (DLS), particle size analysis, differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). The results show that the optimum amount of surfactant not only reduced particle size but also reduced the magnetite properties of Fe3 O4 . It was found that the magnetite behavior of the toner is not similar to the Fe3 O4 used to produce it. Although small-sized Fe3 O4 created toner with a smaller size, toners made with micro Fe3 O4 showed better magnetite properties than toner made with nano Fe3 O4 .